Keefektifan Desain Pembelajaran ELPSA (Experiences, Language, Pictorial, Symbols, Application) Ditinjau dari Hasil Belajar Matematika Siswa pada Materi Relasi Dan Fungsi - Riska Dwi Setiawati; Nyoman Sridana; Baidowi Baidowi; Laila Hayati (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This research aims to determine the effectiveness of the ELPSA (Experiences, Language, Pictorial, Symbols, Application) learning design in terms of the mathematics learning outcomes at VIII grade student of SMPN 1 Utan on the material relations and functions in the academic year 2020/2021. The type of this research is experimental research with posttest only design. The research was conducted in 4 meetings with 3 meetings for the learning process using all ELPSA components and 1 meeting for the implementation of the posttest. The samples were determined by using cluster random sampling technique. The sample is class VIII-1A as an experimental class which is given treatment using the ELPSA learning design. Data collection using observation and test techniques. Instruments include: observation sheets and learning outcomes tests. Learning outcome data is used to find out how far students understand the material being taught and observation data is used to determine the implementation of learning which is analyzed descriptively. Indicators of the effectiveness of the ELPSA learning design, namely if student learning outcomes with a percentage of classical learning completeness of ≥85%. The results showed that there were 14 students who had completed their studies or equal to 87,50% and 2 students who did not complete their studies or 12,50% with an average grade obtained of 82,38. The results of observations of student with active criteria with a percentage of 74% and teacher activities with good criteria with a percentage of 71%.